"It Takes a Virtual Village" Achieving Magnet Redesignation Amidst the COVID-19 Pandemic: Canada's Magnet Hospital Journey. Issue 2 (April 2022) - Jeffs, Lianne; Amaral, Nely; Mundle, William; Amaral, Caleb; Crook, Katelyn; Fung, Emily Y. Y.; Ronald, Kara; Merkley, Jane
Abstract : This article outlines how a Canadian hospital achieved the American Nursing Credentialing Center Magnet Recognition Program redesignation after participating in a virtual site visit (VSV) appraisal process amidst the COVID-19 pandemic. Within our current COVID-19 landscape, being a resilient Magnet-designated organization is paramount. In this context, the American Nurses Credentialing Center (ANCC) has developed a VSV model that (1) extends the use of audio/video (A/V) conferencing technology to showcase nursing excellence; (2) maintains the integrity of the appraisal process; and (3) ensures the safety and well-being of staff, patients and their care partners, and the appraisers. Key narrative insights are highlighted around planning and on-site execution of a successful VSV. The redesignation is a culmination of several stakeholders' efforts who shared their sense of pride, inspiration, and accomplishment during the VSV. The redesignation status notification exemplifies resiliency and was welcomed amidst uncertainty with the evolving COVID-19 pandemic. The planning and on-site implementation plan may serve as a blueprint for others who will be engaged in a VSV as part of their designation or redesignation journey. Insights are shared around preparing for the VSV, hosting the VSV, and achieving the ANCC Magnet Recognition Program redesignation.